The Effect of Competences, Work Motivation, Learning Environment on Human Resource Performance - Mulang, Hastuti (Golden Ratio of Human Resource Management, 2021)
This research is motivated by efforts to improve the quality of education, and teacher performance has not been achieved as expected. This can be seen from the number of students' achievement decreases. Due to the teacher's performance has not yet produced a standard output of students who excel. The cause that occurs can not be separated from the competence, motivation, and learning environment that still has to be improved. These three variables directly or indirectly have an influence on teacher performance and the quality of education. This study aims to determine and analyze the effect of competence, motivation, learning environment on teacher performance, the quality of education, and indirect effects through teacher performance on the quality of education. The population of this study was all elementary school teachers at the Education Office of South Sulawesi Province. The total sample study is 393 respondents. The data were analyzed using the Structural Equation Model (SEM) utilizing AMOS 18. The study results found that direct or indirect effect the competence, motivation, learning environment had a positive and significant effect on teacher performance, as well as relationship antecedent variables on the quality of education. Including the performance of teachers, effect on quality of education.